Genotoxicity and cytotoxicity of gold Nanoparticles - Fatma Alzahraa Sayed Mohammed; Ahmed Soltan Abdelmonem; Monira Mahmoud Rageh; Noha Mohammed Sayed (Cairo : Fatma Alzahraa Sayed Mohammed, 2020)
The aim of this work is to evaluate the cytotoxicity and genotoxicity of pegylated gold nanorods (PEG/GNRs) as photothermal agents. The treatment protocol using PEG/GNRs was compared with that protocol using cisplatin as a regular chemotherapeutic drug. The former formulation found to have a high efficacy in treating tumors induced in experimental animals. The formulation was characterized by measuring its absorption spectra, zeta potential and transmission electron microscope. The cytotoxicity and genotoxicity of mice liver, kidney and tumor tissues were determined by measurement of malondialdehyde (MDA) levels, super oxide dismutase (SOD) activity, DNA damage and observing its histopathological changes.The results showed that the treated mice exhibited decreased levels of SOD in tumor tissues. The induced oxidative stress due to tumor growth in liver and kidney tissues showed a marked decrease indicated by the increase in SOD. The former results were also confirmed by measuring MDA, comet parameters and the histopathological examination. The formulation prepared in this work showed a high efficacy in treating Ehrlich tumor marked by diminishing its volume and so reducing its related oxidative stress on the critical organs
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Biophysics
Issued also as CD
Keywords: Cytotoxicity; Genotoxicity; Gold nanorods